2011
DOI: 10.1016/j.jcin.2010.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The SPIRIT V Study

Abstract: Use of EES in patients with multiple, complex de novo lesions yielded 1-year major adverse cardiac events, stent thrombosis, and target lesion revascularization rates that are comparable to those of the more controlled SPIRIT II and SPIRIT III trials-which included patients with restricted inclusion/exclusion criteria-and other all-comer population, physician-initiated studies like the X-SEARCH (Xience Stent Evaluated At Rotterdam Cardiology Hospital) and COMPARE (A Randomized Controlled Trial of Everolimus-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Additional studies will be required to address the unique protein adsorption behavior of PVDF-HFP and how that relates to the clinical observation of satisfactory fluoropolymer performance. 30,[50][51][52] In fact, fluoropolymers have long been a preferred group of materials for blood contact applications. [53][54][55] Furthermore, PVDF-HFP has favorable mechanical properties to perform as a durable coating for substrates that are subject to deformation (as are stents).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additional studies will be required to address the unique protein adsorption behavior of PVDF-HFP and how that relates to the clinical observation of satisfactory fluoropolymer performance. 30,[50][51][52] In fact, fluoropolymers have long been a preferred group of materials for blood contact applications. [53][54][55] Furthermore, PVDF-HFP has favorable mechanical properties to perform as a durable coating for substrates that are subject to deformation (as are stents).…”
Section: Discussionmentioning
confidence: 99%
“…[53][54][55] Furthermore, PVDF-HFP has favorable mechanical properties to perform as a durable coating for substrates that are subject to deformation (as are stents). 56 In large clinical studies, PVDF-HFP coated stents have demonstrated lower levels of acute and late state thrombosis 30 compared to other stents, although release of antiproliferative agents, variability in stent design, and coating processing technologies used complicate simple conclusions about the contribution of the biomaterials themselves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies include the SPIRIT V study, XIENCE V USA, and XIENCE V India. In the SPIRIT V study, the 1-year rates of MACE, stent thrombosis, and target lesion revascularization in complex patients were similar to those observed in the simple patient populations included in the SPIRIT II and III trials 31. Through 2 years, the rate of definite or probable stent thrombosis was low (0.79%) 32.…”
Section: Clinical Studiesmentioning
confidence: 53%
“…There are an ample number of studies available for the DP-coated EES. 14 , 17 , 18 , 19 The MACE rates at 12 months were 5.1% according to the SPIRIT V study, 17 one of the benchmark studies for the Xience V EES. The results are comparable with those of the present study, where 12-month MACE rates were 4.9% in the DP-EES group and 4.2% in the BDP-EES group.…”
Section: Discussionmentioning
confidence: 99%